Anti-precipitation composite absorbent as well as preparation method and application thereof
By using anti-precipitation composite absorber in electromagnetic wave absorbing materials, the density matching between hollow glass microspheres and magnetic absorber and the bonding effect of the adhesive are solved, and the magnetic absorber settlement problem is realized. Uniformity and efficient absorption performance.
Patent Information
- Application Number
- CN202411459604.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-07
AI Technical Summary
The magnetic absorbent tends to settle in the dispersed glue liquid, resulting in uneven finished products of electromagnetic wave absorbing materials and high density leading to poor stability of the dispersion system.
Anti-precipitation composite absorber is made of hollow glass microspheres, magnetic absorber and binder. By controlling density and particle size and combining with the use of binder, a density-matched composite absorber is prepared to improve dispersion stability and Absorption performance.
The uniform dispersion of magnetic absorbents in the absorbing cell and the absorbing foam is achieved, the absorption performance under equal mass loading is improved, the settlement problem is avoided, and the uniformity and performance of the finished product are ensured.
Smart Images

Figure CN119277745A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of functional materials, and in particular to an anti-precipitation composite absorbent and a preparation method and application thereof. Background Art
[0002] Electromagnetic wave absorbing materials are a type of material that can effectively absorb electromagnetic waves and dissipate them by converting them into heat or dissipating them through interference effects. Among various electromagnetic wave absorbing materials, magnetic absorbent is an absorbing material that dissipates electromagnetic energy through magnetic loss. There are many types of magnetic absorbents, such as carbonyl iron powder, ferroferric oxide, ferrite magnetic fiber, etc. Among them, carbonyl iron powder is the most popular because it has high magnetic permeability and temperature stability and is widely used.
[0003] Magnetic absorbers can be used in absorbing materials such as absorbing honeycombs, absorbing films and absorbing foams. For example, when used to prepare absorbing honeycombs, the magnetic absorber needs to be prepared into a dispersed glue solution and then attached to the honeycomb surface by dipping. When used to prepare absorbing foams, the magnetic absorber needs to be dispersed in the foam resin. However, most magnetic absorbers have a very high density. For example, the density of carbonyl iron powder reaches 7.85g / cm 3 , the density of ferroferric oxide reaches 5.17g / cm 3 , much higher than the resin glue (about 1.1g / cm 3 ), foam monomer (about 0.9~1.0g / cm 3 ) and common solvents (about 0.8-1.0g / cm 3 ) density, causing the dispersion system to easily settle, resulting in uneven final product. Therefore, it is necessary to solve the stability problem of the dispersion system. Summary of the invention
[0004] The present invention mainly aims at the above problems and proposes an anti-sedimentation composite absorbent and a preparation method. Its purpose is to invent a composite magnetic absorbent with a density matching the existing colloid system and having a high anti-sedimentation ability, and use it to prepare absorbing honeycombs and absorbing foams to solve the problem that the magnetic absorbent is easy to settle in the dispersed colloid.
[0005] The present invention protects an anti-sedimentation composite absorbent and a preparation method thereof. The composite absorbent can be used to prepare wave-absorbing foam and wave-absorbing honeycomb loaded with magnetic absorbent particles with good uniformity, and has better equal mass loading absorption performance.
[0006] The technical solution of the present invention is achieved as follows: the present invention provides an anti-precipitation composite absorbent, which is obtained by solidifying raw materials containing hollow glass microspheres, a magnetic absorbent and a binder;
[0007] The true density of the hollow glass microspheres is 0.15 to 0.45 g / cm 3 , the average particle size is 20 to 80 μm;
[0008] The true density of the anti-precipitation composite absorbent is 0.7 to 1.5 g / cm 3 , the average particle size is 20 to 800 μm.
[0009] Optionally, the true density of the hollow glass microspheres is independently selected from 0.15 g / cm 3 , 0.2g / cm 3 , 0.25g / cm 3 , 0.3g / cm 3 , 0.35g / cm 3 , 0.4g / cm 3 , 0.45g / cm 3 Any value in or a range between any two of the above.
[0010] Optionally, the average particle size of the hollow glass microspheres is independently selected from any value of 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, or a range between any two of the above values.
[0011] Optionally, the true density of the anti-precipitation composite absorbent is independently selected from 0.7 g / cm 3 , 0.8g / cm 3 , 0.9g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 Any value in or a range between any two of the above.
[0012] Optionally, the average particle size of the anti-precipitation composite absorbent is independently selected from any value of 20 μm, 50 μm, 100 μm, 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm or a range between any two of the above values.
[0013] Optionally, the magnetic absorbent is selected from at least one of flaky carbonyl iron powder, spherical carbonyl iron powder, and ferrosoferric oxide particles.
[0014] Optionally, the binder is a moisture-dissipating heat-curable resin with a concentration of 0.5 to 3 wt %;
[0015] The moisture heat dissipation curing resin is selected from at least one of bismaleimide resin, epoxy resin, polyamic acid salt and acrylate.
[0016] According to another aspect of the present application, a method for preparing the above-mentioned anti-precipitation composite absorbent is provided, and the preparation method comprises:
[0017] According to the formula m1:m2=(C / B-1) / (1-C / A)×(0.9-1.0), the magnetic absorbent and the hollow glass microsphere raw materials are weighed, mixed, and then the binder solution is added, stirred, dried to remove the solvent, and pre-cured, and the pre-cured mixture is gently crushed and fully cured again to obtain the anti-sedimentation composite absorbent;
[0018] In the formula m1:m2=(C / B-1) / (1-C / A)×(0.9~1.0), m1 is the mass of the magnetic absorbent, m2 is the mass of the hollow glass microspheres, A is the true density of the magnetic absorbent, B is the true density of the hollow glass microspheres, and C is the true density of the anti-sedimentation composite absorbent.
[0019] Optionally, the true density of the hollow glass microspheres is 0.15 to 0.3 g / cm 3 ;
[0020] The true density of the anti-precipitation composite absorbent is 0.8-1.3 g / cm 3 , the average particle size is 150~500μm.
[0021] Optionally, the amount of the binder solution is 30-50% of the volume of the hollow glass microspheres.
[0022] Optionally, the amount of the binder solution used is any value independently selected from 30%, 35%, 40%, 45%, 50% of the volume of the hollow glass microspheres, or a range between any two of the above values.
[0023] Optionally, the concentration of the binder solution is 0.5-3%.
[0024] Optionally, the concentration of the binder solution is independently selected from any value of 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, or a range between any two of the above.
[0025] Optionally, the raw materials for preparing the anti-sedimentation composite absorbent also contain carbon nanotubes or graphene.
[0026] Optionally, the stirring time is 5 to 30 minutes.
[0027] Optionally, the stirring time is independently selected from any value among 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, or a range between any two of the above.
[0028] According to another aspect of the present application, there is provided a use of the above-mentioned anti-precipitation composite absorber in microwave-absorbing foam and microwave-absorbing honeycomb products.
[0029] To achieve the above object, the present invention provides an anti-sedimentation composite absorbent, which is composed of hollow glass microspheres, magnetic absorbent particles, and a binder. The real density of the anti-sedimentation composite absorbent is 0.7-1.5 g / cm 3 The average particle size is 20-800 μm, and the actual density of the hollow glass microspheres is 0.15-0.45 g / cm 3 , the average particle size is 20 to 80 μm.
[0030] A method for preparing an anti-sedimentation composite absorbent comprises the following steps: mixing magnetic absorbent particles with hollow glass microspheres, wherein the masses m1 and m2 of the two are controlled to be m1:m2=(C / B-1) / (1-C / A)×(0.9-1.0) according to the density A of the magnetic absorbent, the true density B of the hollow glass microspheres, and the true density C of the required composite absorbent, and the two are fully mixed; after the mixing, adding a binder solution of 30-50% of the volume of the hollow glass microspheres, wherein the solution concentration is 0.5-3wt%, stirring for 5-30 minutes, drying to remove the solvent, and pre-curing the binder to be cured; and gently crushing the treated mixture, and then fully curing it to obtain the anti-sedimentation composite absorbent.
[0031] The present invention has the following beneficial effects:
[0032] The invention provides an anti-sedimentation composite absorbent and a preparation method thereof. The anti-sedimentation composite absorbent having a density matching that of a conventional resin glue and a solvent is prepared by a method of co-adsorbing a magnetic absorbent on the surface of a hollow glass microsphere and bonding and fixing. The dispersed glue has good stability, and the absorbent in the prepared absorbing honeycomb and absorbing foam is more evenly dispersed. When loaded with the same mass of magnetic absorbent, the absorbent has better absorption performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0034] Figure 1 It is a schematic structural diagram of the anti-sedimentation composite absorbent of the present invention;
[0035] Figure 2 This is a principle analysis diagram of the electromagnetic wave absorption enhancement of the present invention. DETAILED DESCRIPTION
[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] The present invention protects an anti-sedimentation composite absorbent and a preparation method thereof. The composite absorbent can be used to prepare wave-absorbing foam and wave-absorbing honeycomb loaded with magnetic absorbent particles with good uniformity, and has better equal mass loading absorption performance.
[0038] The specific implementation of an anti-sedimentation composite absorbent and a preparation method thereof is as follows: the anti-sedimentation composite absorbent is composed of hollow glass microspheres, magnetic absorbent particles, and a binder, and the true density of the anti-sedimentation composite absorbent is 0.7 to 1.5 g / cm 3 The average particle size is 20-800 μm, and the actual density of the hollow glass microspheres is 0.15-0.45 g / cm 3 , the average particle size is 20-80 μm. The preparation process is as follows: the magnetic absorbent particles are mixed with hollow glass microspheres, and the masses m1 and m2 of the two are controlled as m1:m2=(C / B-1) / (1-C / A)×(0.9-1.0) according to the true density A of the magnetic absorbent, the true density B of the hollow glass microspheres, and the true density C of the required composite absorbent, and the two are fully mixed; after the mixing is completed, a binder solution of 30-50% of the volume of the hollow glass microspheres is added, and the solution concentration is 0.5-3%, and after stirring for 5-30 minutes, the solvent is removed by drying, and the binder to be cured is pre-cured; the treated mixture is gently crushed, and then fully cured to obtain an anti-sedimentation composite absorbent.
[0039] The anti-sedimentation composite absorbent and the preparation method thereof provided by the present invention will be described in detail with reference to specific examples.
[0040] Example 1
[0041] The implementation process of the technical solution of this embodiment is as follows:
[0042] (1-1) Prepare a density matching water (1g / cm3 ) of the anti-sedimentation composite magnetic absorbent, taking flake carbonyl iron powder (7.86g / cm 3 ) 1000g, hollow glass microspheres 291g (brand K25, average diameter 65μm, true density 0.25g / cm 3 , bulk density 0.15g / cm 3 , volume 1940 mL), the two were mixed together, and stirred thoroughly with a stirrer for 3 h to obtain a mixture.
[0043] (1-2) 700 g of a 1 wt% aqueous solution of polyvinyl alcohol was added to the mixture obtained above, and after stirring for 10 min, the mixture was placed in an oven at 130° C. to remove water. After the dried solid was fully dried, it was gently crushed and sieved with a 20-mesh sieve to obtain an anti-sedimentation composite absorbent with an average particle size of about 320 μm.
[0044] (1-3) E51 epoxy resin emulsion (50%) was diluted to 20%, an equivalent amount of curing agent isophorone diamine was added, and then an anti-settling composite absorbent was added, with a content of 20wt%, and stirred to obtain a dispersed adhesive solution, which was then used for impregnation of microwave-absorbing honeycombs, and the front and back sides were impregnated 3 times respectively.
[0045] (1-4) In the above (1-1), the amount of hollow glass microspheres is increased to 306 g (volume is 2040 mL), and the other steps are the same to obtain an anti-sedimentation composite absorbent with an average particle size of 296 μm.
[0046] The anti-sedimentation composite absorbent obtained in Example 1 (using the ratio in (1-1)) has good suspension in the water-dispersible glue system. After three days of placement, only 15.3wt% of the particles settle (when pure magnetic nanoparticles are used, 99wt% settle within 20 minutes). The particles can be restored to their original state by a little stirring and are evenly distributed on the surface of the impregnated honeycomb. The anti-sedimentation composite absorbent using the ratio (1-4) has slightly improved suspension in the water-dispersible glue system. After three days of placement, the sedimentation rate is 11.6wt%. The specific experimental results are shown in Table 1.
[0047] Example 2
[0048] The implementation process of the technical solution of this embodiment is as follows:
[0049] (2-1) Prepare a density-matched PMI foam polymerization monomer (0.95 g / cm 3 ) of the anti-sedimentation composite magnetic absorbent, taking spherical carbonyl iron powder (7.86g / cm 3 )1000g, hollow glass microspheres (brand K20, average diameter 65μm, true density 0.20g / cm 3 , bulk density 0.13g / cm 3, volume 1800mL) 234g, the two were mixed together, and stirred thoroughly for 4h using a shaker to obtain a mixture.
[0050] (2-2) 850 g of 1.5 wt% bismaleimide resin acetone solution was added to the mixture obtained above. The brand of bismaleimide resin is QY9611. After stirring for 15 min, the wet sandy mixture was placed in a vacuum distiller to remove acetone by vacuum to obtain a dry solid. The solid was then cured in an oven at 150°C for 0.5 h. After curing, it was gently crushed, sieved with a 40-mesh sieve, and then cured in an oven at 200°C for 2 h to obtain an anti-sedimentation composite absorbent with an average particle size of about 120 μm. It is mainly composed of hollow glass microspheres attached with single and 2 to 5 agglomerated carbonyl iron powders.
[0051] (2-3) Take 50g of methacrylic acid, 50g of methacrylonitrile, 3g of acrylamide, 6g of formamide and 0.01g of azobisisobutyronitrile, mix them evenly, then add 60g of the above-prepared anti-settling composite absorbent, the content is 35.5wt%, stir to obtain a dispersed colloid, then polymerize at 40°C for 72h to obtain a polymerized solid. Heat the polymerized solid to 210°C for foaming for 1h, then complete imidization at 160°C to obtain a PMI absorbing foam.
[0052] The anti-sedimentation composite absorbent obtained in Example 2 has good suspension in the PMI polymer monomer, and is evenly dispersed in the polymer solid after a long period of polymerization, with only a small amount of sedimentation at the bottom (while when pure magnetic nanoparticles are used, they completely settle within 10 minutes), and the obtained PMI foam has good wave absorption performance. The specific experimental results are shown in Table 1 below.
[0053] Example 3
[0054] The implementation process of the technical solution of this embodiment is as follows:
[0055] (3-1) Prepare a density-matched epoxy resin (1.1 g / cm 3 ) of the anti-sedimentation composite magnetic absorbent, taking ferroferric oxide nanoparticles (5.17 g / cm 3 ) 1000g, hollow glass microspheres 323g (brand S32, average diameter 40μm, true density 0.32g / cm 3 , bulk density 0.2g / cm 3 , volume: 1615 mL), the two were mixed together, and stirred thoroughly for 4 h using a stirrer to obtain a mixture.
[0056] (3-2) The mixture obtained above was added with 2 wt% E51 epoxy resin and 680 g of aqueous dispersion emulsion in which 0.85 g of dicyandiamide was dissolved, stirred for 10 min, and then placed in an oven at 130° C. to remove water. After the dried solid was fully dried, it was heated to 140° C. and kept for 30 min. After cooling, it was gently crushed and sieved with a 20-mesh sieve. The powder was then post-cured at 180° C. for 2 h to obtain an anti-sedimentation composite absorbent with an average particle size of about 170 μm.
[0057] (3-3) Take 52g of E51-7, 250g of curing agent 4,4'-diaminodiphenylmethane, 90g of foaming agent OBSH, and then add 300g of anti-settling composite absorbent (content is 21.6wt%), stir evenly to obtain a dispersed adhesive solution, and then use it for heating and foaming to prepare foam, to obtain epoxy resin absorbing foam.
[0058] The anti-sedimentation composite absorbent obtained in Example 3 has good suspension in the epoxy resin glue, and no sedimentation is observed during the foaming process, while the sedimentation is very obvious when only the magnetic nanoparticles are used. The specific experimental results are shown in Table 1 below.
[0059] Example 4
[0060] The implementation process of the technical solution of this embodiment is as follows:
[0061] (4-1) Prepare a density-matched water (1 g / cm 3 ) of the anti-sedimentation composite magnetic absorbent, taking flake carbonyl iron powder (7.86g / cm 3 ) 1000g, hollow glass microspheres 218g (brand K20, average diameter 65μm, true density 0.20g / cm 3 , bulk density 0.13g / cm 3 , volume of 1677 mL), the two were mixed together, and stirred thoroughly with a stirrer for 3 h to obtain a mixture.
[0062] (4-2) 700 g of 2 wt% carbon nanotube dispersion was added to 4 g of 0.57 wt% polyvinyl alcohol, which was heated to dissolve uniformly, and then the above mixture was added thereto, stirred for 10 min until uniformly mixed, and then placed in an oven at 130°C to dry to remove water. After the dried solid was fully dried, it was gently crushed and sieved with a 30-mesh sieve to obtain an anti-sedimentation composite absorbent with an average particle size of about 207 μm.
[0063] (4-3) E51 epoxy resin emulsion (50%) was diluted to 20%, and an equivalent amount of curing agent isophorone diamine was added, followed by adding an anti-settling composite absorbent with a content of 25wt%, and stirred to obtain a dispersed adhesive solution, which was then used for impregnation of the microwave-absorbing honeycomb, with the front and back sides impregnated 3 times respectively.
[0064] (4-4) The carbon nanotubes in the above (4-2) are replaced with graphene, and the other steps are the same to obtain an anti-sedimentation composite absorbent with an average particle size of 320 μm.
[0065] (4-5) In the above (4-1), the amount of hollow glass microspheres is increased to 240 g (volume is 1846 mL), and the other steps are the same to obtain an anti-sedimentation composite absorbent with an average particle size of 182 μm.
[0066] The anti-sedimentation composite absorbent containing carbon nanotubes obtained in Example 4 (at the ratio in step (4-1)) has good suspension in the water-dispersible glue system. After three days, only 14.5wt% of the composite absorbent has settled. It can be restored to its original state by a little stirring. The composite absorbent obtained by impregnating honeycombs with the glue has a very uniform distribution on the surface of the honeycombs. After three days, 19.1wt% of the anti-sedimentation composite absorbent containing graphene has settled in the water-dispersible glue system. After appropriately increasing the amount of hollow glass microspheres in (4-5) of Example 4, the suspension of the anti-sedimentation composite absorbent in the water-dispersible glue system is slightly improved, and the sedimentation rate after three days is reduced to 8.2wt%. The specific experimental results are shown in Table 1 below.
[0067] Example 5
[0068] The implementation process of the technical solution of this embodiment is as follows:
[0069] (5-1) Prepare a density-matching epoxy resin (1.1 g / cm 3 ) anti-sedimentation composite magnetic absorbent, flake carbonyl iron powder (7.86g / cm 3 ) 1000g, hollow glass microspheres 227g (brand XLD3000, average diameter 30μm, true density 0.23g / cm 3 , bulk density 0.135g / cm 3 , volume: 1681 mL), the two were mixed together, and stirred thoroughly for 4 h using a stirrer to obtain a mixture.
[0070] (5-2) 680 g of water-based dispersed epoxy resin emulsion AG80 in which the curing agent dicyandiamide was dissolved was added to the mixture obtained above with a total concentration of 2.5 wt%, and the mixture was stirred for 10 min, and then placed in an oven at 130° C. to remove water. After the dried solid was fully dried, the temperature was raised to 135° C. and maintained for 30 min. After cooling, the solid was gently crushed and sieved with a 20-mesh sieve. The powder was then post-cured at 180° C. for 2 h to obtain an anti-sedimentation composite absorbent with an average particle size of about 145 μm.
[0071] (5-3) Prepare 600 g of epoxy resin (AG80 400 g + DDS 200 g), add 500 g of anti-settling composite absorbent (content is 45 wt%), and press to obtain a wave-absorbing adhesive film with a thickness of 2 mm.
[0072] The absorbing film obtained in Example 5 has good storage stability, the absorbent will not be enriched at the bottom during storage or curing, and the absorbing capacity of the cured film is much higher than that of a conventional film with the same absorbent loading (i.e., a film coated with the same mass of absorbent and resin). The specific experimental results are shown in Tables 1 and 2.
[0073] Test Example 1
[0074] The anti-sedimentation composite magnetic absorbent prepared in Examples 1 to 5 was tested for anti-sedimentation. During the test, the anti-sedimentation composite magnetic absorbent was added to the matching system, the addition amount was controlled to be 25wt%, and the composite absorbent was fully stirred for 30min to achieve dispersion equilibrium in the matching system, and then placed for natural sedimentation for 3h, and the sedimentation state was observed. The sedimentation ratio of 10-20wt% was a small amount of sedimentation, and the sedimentation ratio of 2-10wt% was a trace amount of sedimentation. When it was less than 2wt%, it could be regarded as basically no sedimentation. During the test, the test temperature was 25°C and the ambient humidity was 40-60%. The specific experimental results are shown in Table 1. As a comparison, when a non-composite magnetic absorbent was used, complete sedimentation (90-100wt%) occurred in low-viscosity matching systems such as Examples 1, 2, and 4, and partial sedimentation (about 35wt% and about 70wt%, respectively) occurred in high-viscosity matching systems such as Examples 3 and 5.
[0075] Table 1. Technical conditions of each embodiment and main properties of the anti-sedimentation composite magnetic absorbent
[0076]
[0077]
[0078] Table 2. Comparison of reflectivity of Example 5 and films with the same loading and thickness
[0079]
[0080] It can be seen from Table 2 that the anti-sedimentation composite magnetic absorbent prepared in Example 5 of the present invention has a reflectivity greater than that of the film with the same loading and thickness prepared in the conventional system, and the anti-sedimentation composite absorbent prepared in the present invention has better absorption performance.
[0081] The present invention prepares an anti-sedimentation composite absorbent by a simple and easy method, and its true density can be between 0.15 and 1.5 g / cm 3In order to achieve good density control and anti-settling effect, the present invention adopts multiple measures such as (1) final density range control, (2) average particle size optimization, and (3) adhesive bonding technology scheme, which are described in detail as follows:
[0082] (1) In order to match the density of commonly used resins, solvents, and polymer monomers (0.8-1.2 g / cm 3 ), its actual density is controlled to be 0.7~1.5g / cm 3 , can obtain better anti-sedimentation performance. When the density is higher, the anti-sedimentation ability of the composite absorbent decreases, and the sedimentation gradually increases after placement. More preferably, the matching density is 0.8-1.3g / cm 3 , avoiding individual density fluctuations caused by errors such as microsphere breakage and adsorption dispersion differences, and almost no sedimentation occurs. The actual density of the hollow glass microspheres used is 0.15-0.45g / cm 3 The average particle size is 20-80 μm, which can avoid the fragility of hollow microspheres and the decrease in density control accuracy. More preferably, it is 0.15-0.3 g / cm 3 , a higher mass ratio of magnetic nanoparticles can be obtained. In order to obtain a composite absorbent that meets the density requirements, during preparation, the mass ratio of the magnetic absorbent and the hollow glass microspheres is preferably m1:m2=(C / B-1) / (1-C / A)×(0.9-1.0), where m1 is the mass of the magnetic absorbent, m2 is the mass of the hollow glass microspheres, A is the true density of the magnetic absorbent, B is the true density of the hollow glass microspheres, and C is the true density of the anti-sedimentation composite absorbent. When B≤0.2, the microspheres are more likely to break, and m1:m2 is preferably controlled to 0.9-0.95, at which time a better density match can be obtained. For example, in Example 1, m1:m2 is adjusted to 0.95, and the sedimentation rate drops from 15.3wt% to 11.6%. In Example 4, m1:m2 is adjusted to 0.908, and the sedimentation rate drops from 14.5wt% to 8.2%, and the actual density of the composite absorbent drops to 1.09, which is closer to the matching system, but a further decrease in m1:m2 will lead to an increase in suspended matter. When B≥0.25, the microsphere breakage rate in the composite absorbent obtained by the two-stage solidification method is low, and m1:m2 is preferably controlled to 0.95-1.0, and even without considering the process damage of the microspheres (controlled to 1.0), a relatively satisfactory anti-sedimentation performance can be obtained.
[0083] (2) The anti-sedimentation performance of the anti-sedimentation composite absorbent in the present invention in the glue solution is not only related to its average density, but also to its density distribution and particle size, as shown in Table 3 (taking the system of Example 1 as an example). When the particle size is higher than 800 μm, although its density dispersibility is small, the slight difference between it and the density of the glue solution will make it easy to precipitate, so it is necessary to control the average particle size to 20 to 800 μm. However, when the particles are too small, their density dispersibility is large, causing some particles to float and some particles to settle. The reason is that some microspheres are damaged during crushing, resulting in a higher density in some parts of the powder. Therefore, according to the screening results, the preferred particle size is 120 to 500 μm, at which time the anti-sedimentation composite absorbent has the best anti-sedimentation ability.
[0084] Table 3. Typical particle size and density discreteness, anti-sedimentation change trend
[0085]
[0086] (3) A binder is used to make the magnetic absorbent nanoparticles adhere well to the surface of the hollow glass microspheres, avoiding the desorption of the two caused by the flow of the glue. A binder solution of 30-50% of the accumulated volume of the hollow glass microspheres is added, and the solution concentration is 0.5-3%. When the amount of binder solution is small, the magnetic particles on the surface of the microspheres are unevenly bonded, resulting in partial debonding when dispersed in the glue solution, forming sediment. When the amount is too high, the magnetic particles are desorbed when the binder is added, which increases the sediment when it is dispersed in the glue solution. When the amount of binder is within this range, not only is the adsorption uniform, but the binder solution also plays a capillary role when it dries, so that the magnetic absorbent nanoparticles are well attached to the surface of the glass microspheres.
[0087] (4) The material of the present invention has a high requirement for density control. Therefore, it is very important to reduce the adhesion stability of the magnetic particles on the microspheres and reduce the damage to the microspheres. In addition to particle control (reducing the degree of particle refinement can reduce the damage of the microspheres and improve the density controllability, but when the particles are too large, it will lead to increased sedimentation, see Table 3), the present invention adopts two measures to reduce the adhesion stability of the magnetic particles on the microspheres and reduce the damage of the microspheres to the anti-sedimentation composite adsorbent. The first is that the preferred concentration of the binder solution is 0.5-3%. When the concentration is higher than 0.5wt%, the adhesion stability of the magnetic particles on the surface of the microspheres can be ensured, and the shear flow of the glue during the preparation of the glue can be avoided to damage the adhesion, so that the sedimentation is reduced; by controlling the concentration of the binder solution to be lower than 3wt%, the microspheres are less bonded to each other, and the particles are rarely damaged during refinement. Secondly, it is found that when a thermosetting resin is used, a two-stage curing method is used, that is, the first stage is prepolymerized to obtain a highly brittle semi-cured resin in a room temperature solid state, which is crushed and then post-cured. Compared with the one-step full curing method, the damage to the microspheres can be effectively reduced, as shown in Table 4 (the hollow glass microspheres and magnetic particles used are the same as those in Example 2). The actual density of the microspheres obtained by the two-stage curing is closer to the design density. More preferably, a moisture heat-dissipating curing resin is used with a concentration of 0.5 to 3wt%, which can reduce the damage ratio of the microspheres while achieving bonding, and is economical and environmentally friendly.
[0088] Table 4. Different curing methods
[0089]
[0090] (1) Through experiments, it was found that hollow glass microspheres significantly improved the dispersibility of magnetic nanoparticles under dry conditions, and good dispersion can be obtained using only conventional stirring. Conventional stirring often requires several hours of ball milling to achieve good dispersion when adding magnetic nanoparticles to resin glue. Due to the relatively large diameter of the hollow glass microspheres, they have a sand milling effect under dry stirring conditions, and due to their high surface polarity, they have a strong adsorption effect on magnetic nanoparticles. The presence of the microspheres prevents the reagglomeration of magnetic nanoparticles, so a good dispersion effect is achieved. In particular, it has the best improvement effect on flaky carbonyl iron powder that is difficult to disperse.
[0091] (2) The coexistence of hollow glass microspheres improves the absorption performance when the same mass of absorbent is loaded. Taking Example 5 as an example, after 4 layers of the film are laid and cured, its average reflectivity at 8 to 12 GHz is -11.3 dB, while the direct use of the same mass of flaky carbonyl iron powder is only -5.8 dB. This is due to the special spherical structure of the hollow glass microspheres, which not only effectively disperses the flaky carbonyl iron powder evenly on its surface, but also its refraction and reflection effects increase the number of electromagnetic wave absorptions. In addition, this may also be related to the increase in the uniformity of the dispersion of the absorbent and the reduction in its thin-layer distribution. The principle is analyzed as follows Figure 2 As shown, due to the low dielectric constant of the hollow glass microspheres, compared with absorbers with high loading density, electromagnetic waves can more easily enter the interior of the material without producing strong reflection. In addition, since the hollow glass microspheres are spherical structures and the absorbers are distributed on the surface of the hollow glass microspheres, electromagnetic waves that are not completely absorbed are refracted when they penetrate the absorber layer and enter the hollow glass microspheres, changing the propagation route, making the propagation route in the film layer more tortuous and changeable, greatly improving the absorption rate. The above results in electromagnetic waves in this material having lower reflection and higher absorption than ordinary resins loaded with the same mass of absorbers.
[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An anti-precipitation composite absorbent, characterized in that: The anti-precipitation composite agent is obtained by solidifying raw materials containing hollow glass microspheres, a magnetic absorbent and a binder; The true density of the hollow glass microspheres is 0.15 to 0.45 g / cm 3 , the average particle size is 20 to 80 μm; The true density of the anti-precipitation composite absorbent is 0.7 to 1.5 g / cm 3 , the average particle size is 20 to 800 μm.
2. The anti-precipitation composite absorbent according to claim 1, characterized in that: The magnetic absorbent is selected from at least one of flaky carbonyl iron powder, spherical carbonyl iron powder and ferrosoferric oxide particles.
3. The anti-precipitation composite absorbent according to claim 1, characterized in that: The binder is a moisture-dissipating heat-curing resin with a concentration of 0.5 to 3 wt%; The moisture heat dissipation curing resin is selected from at least one of bismaleimide resin, epoxy resin, polyamic acid salt and acrylate.
4. The method for preparing the anti-precipitation composite absorbent according to any one of claims 1 to 3, characterized in that: The preparation method comprises: According to the formula m1:m2=(C / B-1) / (1-C / A)×(0.9-1.0), the magnetic absorbent and the hollow glass microsphere raw materials are weighed, mixed, and then the binder solution is added, stirred, dried to remove the solvent, and pre-cured, and the pre-cured mixture is gently crushed and fully cured again to obtain the anti-sedimentation composite absorbent; In the formula m1:m2=(C / B-1) / (1-C / A)×(0.9~1.0), m1 is the mass of the magnetic absorbent, m2 is the mass of the hollow glass microspheres, A is the true density of the magnetic absorbent, B is the true density of the hollow glass microspheres, and C is the true density of the anti-sedimentation composite absorbent.
5. The preparation method according to claim 4, characterized in that: The true density of the hollow glass microspheres is 0.15 to 0.3 g / cm 3 ; The true density of the anti-precipitation composite absorbent is 0.8-1.3 g / cm 3 , the average particle size is 150~500μm.
6. The preparation method according to claim 4, characterized in that: The amount of the binder solution is 30-50% of the volume of the hollow glass microspheres.
7. The preparation method according to claim 4, characterized in that: The concentration of the binder solution is 0.5-3%.
8. The preparation method according to claim 4, characterized in that: The raw materials for preparing the anti-sedimentation composite absorbent also contain carbon nanotubes or graphene.
9. The preparation method according to claim 4, characterized in that: The stirring time is 5 to 30 minutes.
10. Use of the anti-precipitation composite absorbent according to any one of claims 1 to 3 in microwave-absorbing foam and microwave-absorbing honeycomb products.